1996
DOI: 10.1016/0735-1097(96)00003-4
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of the admission electrocardiogram in acute myocardial infarction

Abstract: Distortion of the terminal portion of the QRS complex on the admission ECG is independently associated with a higher hospital mortality rate in patients with acute myocardial infarction given thrombolytic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
53
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(59 citation statements)
references
References 45 publications
5
53
1
Order By: Relevance
“…Some of these changes are considered to represent already necrotic areas (Q waves), but other, potentially reversible changes in the QRS complex also appear, although they are less well understood and are usually not considered for clinical decision making. Earlier studies on depolarization changes during ischemia due to acute coronary occlusion have considered QRS prolongation (1)(2)(3)(4)(5), amplitude changes of the R-and S-waves (4,6,7), "distortion" of the terminal part of the QRS complex (8)(9)(10)(11)(12) as well as changes in the high-frequency components of the QRS complex (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these changes are considered to represent already necrotic areas (Q waves), but other, potentially reversible changes in the QRS complex also appear, although they are less well understood and are usually not considered for clinical decision making. Earlier studies on depolarization changes during ischemia due to acute coronary occlusion have considered QRS prolongation (1)(2)(3)(4)(5), amplitude changes of the R-and S-waves (4,6,7), "distortion" of the terminal part of the QRS complex (8)(9)(10)(11)(12) as well as changes in the high-frequency components of the QRS complex (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…In the Sclarovsky-Birnbaum ischemia grading system distortion of the terminal part of the depolarization, in addition to pronounced ST elevation (grade 3 ischemia), has in several studies been found to be a sign of more severe myocardial ischemia and predict larger infarct size, lesser degree of ST-segment resolution, impaired microvascular patency and worse clinical outcome after revascularization by either thrombolysis or primary PCI (8)(9)(10)(11). These changes have been reported to be stronger predictors of clinical outcome than ST measures alone.…”
Section: Introductionmentioning
confidence: 99%
“…5 The magnitude and extent of these ECG changes depend on the size and location of the ischemic/infarcted region and the relationship of this region to the spatial orientation of the particular ECG lead. The size and location of the affected region depend, in turn, on the coronary artery involved, the site of occlusion within the artery, and the presence or absence of collateral circulation.…”
mentioning
confidence: 99%
“…We evaluated the presence or absence of terminal QRS distortion on the admission ECG using the definition of Birnbaum et al: [7][8][9][10] (1) pattern A = emergence of the J point at ≥50% of the R-wave amplitude in leads with qR configuration; or (2) pattern B = disappearance of the S waves in leads with an Rs configuration (leads V1-V3). Distortion of the terminal portion of the QRS complex was defined as pattern A and/or pattern B in at least 2 adjacent precordial leads.…”
Section: Twelve-lead Ecgsmentioning
confidence: 99%
“…[1][2][3][4][5][6] In these studies, much attention has been paid to the magnitude of ST-segment elevation, such as the sum of ST-segment elevation or the number of leads with ST-segment elevation. In contrast, the QRS morphology on the admission ECG in patients with AMI has been paid little attention, but was recently investigated by Birnbaum et al [7][8][9][10] who found that a specific QRS morphology (ie, distortion of the terminal portion of the QRS complex) is independently associated with increased in-hospital mortality in these patients. However, the relation of this ECG finding to the time course of left ventricular (LV) wall motion is unclear, so we sought to clarify this relationship in the healing stage of a first anterior AMI.…”
mentioning
confidence: 99%